Effects of Layering Milling Technology on Distribution of Green Wheat Main Physicochemical Parameters. (28th September 2017) - Tian, Shuang-Qi; Li, Yong-Heng; Chen, Zhi-Cheng; Qiao, Yong-Feng
Abstract : With layered milling flour technology, the efficiency of the nutrient distribution and hardness was demonstrated with the green and normal wheat separation milling. The results showed that the total content of amino acid in green wheat was 8.3%–13.0% higher compared to the common wheat. Comparing the main nutriments Se, Fe, and Ca between green wheat and common wheat, the results showed that different milling treatment methods are capable of separating the different wheat flour from endosperms, bran, and aleurone layers. Micro- and physicochemical characterization of different wheat flour and layers by means of microscopy techniques and images analysis provided relevant qualitative and quantitative information, which can be useful for the study of the microstructure of green and normal wheat products and also for its processing and utilization.